Pan-cancer analysis of trophinin-associated protein with potential implications in clinical significance, prognosis, and tumor microenvironment in human cancers - Li, Zhenfen; Pu, Zhangya; Yang, Ziyue; Zhu, Yuanyuan; Deng, Ying; Li, Ning; Peng, Fang (Frontiers in Oncology, 2022)
Background: Trophinin-associated protein (TROAP), a cytoplasmic protein, is essential for microtubule cytoskeleton assembly. Mounting evidence demonstrates the vital role of TROAP in regulating the proliferation and migration of cells, but it is unclear how it contributes to cancer progression. Methods: The online portals of GEPIA2, Cancer Cell Line Encyclopedia, UALCAN, Human Protein Atlas, and PrognoScan were used to analyze TROAP expression in various tumors and further evaluate its correlation with prognosis. With Western blot and quantitative real-time PCR analysis, we validated TROAP expression levels in hepatocellular carcinoma (HCC) and colorectal cancer (CRC). Ten pairs of HCC and CRC tissues were selected for immunohistochemistry to determine TROAP expression levels in tumors and adjacent tissues, respectively. TROAP knockdown in CRC and HCC cells to verify its role in malignant phenotypes. The genomic and post-transcriptional alterations of TROAP in tumors were determined using the cBioPortal and SangerBox databases. Also, TISIDB was used to investigate the relationship between TROAP expression and tumor microenvironment(TME) among different cancer types. Moreover, a correlation was found between the expression of TROAP and drug sensitivity using GSCALite and CellMiner databases. Results: TROAP expression was significantly upregulated in most cancer types, which is consistent with our validated experimental results in HCC and CRC cells, and immunohistochemistry results. And a poor prognosis was linked to TROAP aberrant expression. Our findings indicated that malignant phenotypes and tumorigenesis induced by TROAP could be due to an activation of the PI3K/Akt/GSK-3β signaling pathway. Furthermore, we found a correlation between TROAP expression and genomic and post-transcriptional alterations in various tumors, including tumor mutation burden, and microsatellite instability. Next, we demonstrated that TROAP expression was associated with the infiltration of immune cells, such as neutrophils and macrophages, and correlated with immunomodulation-related genes in the TME. Additionally, the potential role of TROAP expression in predicting the sensitivity of drugs, including melphalan and chlorambucil, was demonstrated. Conclusions: Collectively, these findings indicated a significant correlation between TROAP expression and malignant phenotype, functional mechanism, survival possibility, TME,therapeutic potential, and prediction of drug sensitivity in various cancers. Hence, TROAP is a promising biomarker and therapeutic target for predicting cancer outcomes.